2020
DOI: 10.7759/cureus.10102
|View full text |Cite
|
Sign up to set email alerts
|

Pericardiocentesis Indications and Complications: A Retrospective Observational Study in a Tertiary Care Hospital in Karachi, Pakistan

Abstract: Introduction: Pericardiocentesis is crucial for the diagnosis and management of diseases responsible for significant pericardial effusions. Pericardiocentesis was performed the first time by Riolanus for cardiac tamponade. He described the process of trephination of the sternum to remove the abnormally accumulated fluid from the pericardial space. However, with the advancement of expertise in echocardiography assisted procedures, echocardiography-guided diagnostic and therapeutic pericardiocentesis is now cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…A subcostal, apical, or parasternal approach can be used, depending on the ultrasound findings [ 21 , 22 ]. Using echocardiography, success rates are high and complication rates are very low, with major complication rates of 1–3% (although these series are not restricted to pericardiocentesis performed in the resuscitation setting) [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Use Of Ultrasound For Diagnosis In Resuscitationmentioning
confidence: 99%
“…A subcostal, apical, or parasternal approach can be used, depending on the ultrasound findings [ 21 , 22 ]. Using echocardiography, success rates are high and complication rates are very low, with major complication rates of 1–3% (although these series are not restricted to pericardiocentesis performed in the resuscitation setting) [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Use Of Ultrasound For Diagnosis In Resuscitationmentioning
confidence: 99%
“…A recent study in our region has reported malignancy as the most common cause of cardiac tamponade and pericardial effusion requiring pericardiocentesis [ 9 ]. However, patients with malignant pericardial effusion require repeat pericardiocentesis or a pericardiac window if they develop recurrent effusion.…”
Section: Introductionmentioning
confidence: 99%